The Failures of Us-Mexico Immigration and Border Policies Under the Donald Trump Administration - SEPTIANI, Dinda; JUNED, Mansur (Journal of Tourism Economics and Policy, 2025)
The migration problem is already at an urgent stage for a country's national security. The United States has felt the impact of the migration phenomenon changing from positive to negative. Donald Trump as President initiated a policy of building a border wall based on America First by prioritizing national security to realize national interests. This study aims to determine how Donald Trump implemented the immigration policy. Furthermore, whether the policy can be implemented successfully or facing failures depends on the implementation. Through Executive Order 13767, the containment of legal and illegal immigrants and the spread of drugs in the United States. This study uses qualitative methods. Data collection in the form of library research. With analysis using the Van Metter and Van Horn policy implementation method. Which then resulted in the policy being considered unsuccessful. Because Trump's policy stopped in the middle of the road and did not continue with the next President, only negative impacts emerged due to Trump's border wall construction policy.